Pengukuran Kualitas Website Melalui Metode Webqual 4.0 Dan Kepuasan Pengguna Internet Pada OLX.co.id - Rokhadi Rokhadi; Arinto Ilham Ramadhan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This researcher aims to find out the influence of business opportunities on the people of Tuban area, with internet access or social media - consisting of Online Media Usability Variables, Information Quality, Service Interaction, to find out the community's response to buying and selling services through the website. In this study will measure the quality of OLX.co.id website using the dimensions of WebQual 4.0 (Usability, Quality of Information, Service Interaction) and user satisfaction variables. In data analysis techniques use descriptive with statistical calculations. The study data was in the form of questionnaires with 69 - 71 respondents. Data processing is done using IBS SPSS 26. The results of research on the quality of OLX.co.id's website are positive and partially significant influences on user satisfaction OLX.co.id